Improving Linearity and Robustness of RF LDMOS by Mitigating Quasi-Saturation Effect - Haifeng Mo; Yaohui Zhang; Helun Song (Active and Passive Electronic Components)
This paper discusses linearity and robustness together for the first time, disclosing a way to improve them. It reveals that the nonlinear transconductance with device working at quasi-saturation region is significant factor of device linearity. The peak electric field is the root cause of electron velocity saturation. The high electric field at the drift region near the drain will cause more electron-hole pairs generated to trigger the parasitic NPN transistor turn-on, which may cause failure of device. Devices with different drift region doping are simulated with TCAD and measured. With LDD4 doping, the peak electric field in the drift region is reduced; the linear region of the transconductance is broadened. The adjacent channel power ratio is decreased by 2 dBc; 12% more power can be discharged before the NPN transistor turn-on, indicating a better linearity and robustness.